Cancer-related fatigue: quality, credibility, usability, and readability of information on websites of health care institutions in Germany - Wagner, Anna S.; Milzer, Marlena; Steindorf, Karen; Kiermeier, Senta; Schmidt, Martina; Maatouk, Imad (Patient education and counseling, 2024)
Objectives - This study aimed to portray available information on cancer-related fatigue on German health care institution websites considering the idea of patient empowerment. - Methods - Based on website quality criteria, we developed a website-rating tool comprising 18 items. Descriptive analyses, a KruskalWallis test, and corresponding post hoc tests comparing rating sum scores between institution groups were performed. - Results - Websites of 283 systematically compiled health care institutions were included in the rating. Cancer-related fatigue was introduced on 21.9% and detailed information was provided on 27.9% of the websites. Information material was offered on 9.2% of the websites, while fatigue treatment offers were presented on 21.6% of the websites. The rating sum scores differed between institution groups (p < 0.001), with Comprehensive Cancer Centers scoring significantly higher than the others. - Conclusion - The rating revealed an overall sparse provision of information, with fatigue being addressed on less than half of the websites. Practice Implications: For patients who have access to at least one introduction about fatigue, institutions need to extend their websites. Patients could further be referred to external institutions or information booklets. The naming of contact persons may help linking patients to providers.
Gesehen am 10.06.2024